Managerial Ownership and Audit Committee Effects on Integrated Reporting Quality: Moderating Role of Board Gender Diversity - Dewi Wahyuni; Nadirsyah; Nuraini A (Invoice : Jurnal Ilmu Akuntansi, 2026)
This study examines the influence of managerial ownership and audit committee effectiveness on the quality of integrated reporting (IRQ), with the gender of the board of directors as a moderating variable, in companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. Despite the increasing global adoption of integrated reporting, empirical evidence on its governance determinants in emerging markets remains limited and fragmented. This study integrates institutional, legitimacy, and stakeholder theories to provide a comprehensive explanation of governance-driven reporting behavior. Using a quantitative associative approach, this study analyzes 149 firm-year observations from 61 companies selected through purposive sampling. Panel data regression analysis with a Random Effect Model (REM) is employed to test the hypotheses. The results indicate that managerial ownership and audit committees have a positive and statistically significant effect on the quality of integrated reporting, supporting the arguments of agency alignment and effective monitoring mechanisms. However, the gender of the board of directors does not significantly moderate the relationship between governance mechanisms and reporting quality, suggesting contextual and structural limitations in the role of gender diversity within emerging markets. This study contributes to the literature by integrating multiple governance mechanisms within a multi-theoretical framework and providing empirical evidence from Indonesia. Practically, the findings highlight the importance of strengthening corporate governance structures to enhance transparency, accountability, and the overall quality of integrated reporting, offering implications for regulators, policymakers, and standard-setting bodies.